Pelatihan dan Pendampingan Ibu Balita dan Kader tentang Pentingnya Asupan Vitamin A dan Pembuatan Makanan Berbasis Vitamin A - rahmani; Fathurrahman; Sajiman (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2025)
Vitamin A deficiency is a major health problem in developing countries, including Indonesia. KVA especially affects young children, among those who are deficient they can experience xerophthalmia and can result in blindness, limited growth, weakened body defenses, exacerbation of infections and increased risk of death. It is clear that VAD can continue from school age and adolescence to adulthood (Keith and West, 2008). According to data from the Banjar Regency Health Profile, 2021, the coverage of vitamin A provision in Banjar Regency for toddlers (aged 6 – 59 months) is still low, namely 80.1% (RPJMN target is 87%), including in East Martapura District due to, among other things. due to the fact that the work area is difficult to reach, there is still a lack of available health workers, the target is quite large, there is still a large amount of vitamin A entrusted to posyandu cadres and village midwives who do not reach the target, as well as a lack of information to mothers of toddlers about the importance of vitamin intake. A in toddlers and a lack of understanding of the types of foods that contain vitamin A and the correct processing methods. To increase information/knowledge and skills, the method of this community service activity is in the form of providing training and mentoring to mothers of toddlers and cadres about the importance of vitamin A intake and making vitamin A-based foods in Antasan Senor village, East Martapura District, Banjar Regency as an effort to prevent and detect early onset of disease. the problem of vitamin A deficiency in toddlers. The change in knowledge of mothers of toddlers and cadres after providing counseling was an increase of 48.28%. The implementation of community service activities in Antasan Senor Village, East Martapura District, Banjar Regency, which has been carried out, can be explained that the counseling given to groups of mothers of toddlers and cadres has been effective.